PENINGKATAN PERILAKU HIDUP BERSIH DAN SEHAT BAGI PELAKU USAHA SLONDOK PADA MASA PANDEMI COVID-19 DI DESA KENALAN, KECAMATAN BOROBUDUR, KABUPATEN MAGELANG - Wike oktasari (JURNAL KASTARA, 2023)
Clean and healthy living behaviors refer to all health behaviors carried out out of an awareness so that family members can help themselves in the health sector and take an active role in neighborhood health activities. Coronavirus disease-19, known as Covid-19, is a infectious disease. This virus is capable of infecting people of all ages. Covid-19 also has an impact on business practitioners in doing their business. This project included two types of activities: Clean and healthy living behaviors and health and environmental hygiene education. Clean and healthy living behaviors among Slondok business practitioners can be seen from 10 indicators. Participants' blood pressure was tested for free during health education, and environmental hygiene education, including the methode of eracdicating mosquito larvae. The clean and healthy living habits among slondok business practitioners is intended to keep them healthy and able to sustain their production  and also  increasing  the revenue for their families in the face of the Covid-19 pandemies.